2014
DOI: 10.1016/j.catcom.2014.06.026
|View full text |Cite
|
Sign up to set email alerts
|

The selective oxidation of glycerol over model Au/TiO2 catalysts — The influence of glycerol purity on conversion and product selectivity

Abstract: Publication date 2014Publication information Catalysis Communications, 56 : 72-75Publisher ElsevierLink to online version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…Sullivan and Burnham [82] conducted a comparative study on the activity and selectivity of the catalytic oxidation of PG and CG through the Au/TiO 2 catalyst system in an aqueous glycerol solution and an atmospheric pressure environment. In PG oxidation, the conversion of glycerol and the selectivity to DHA are 45% and 64%, respectively.…”
Section: Dhamentioning
confidence: 99%
“…Sullivan and Burnham [82] conducted a comparative study on the activity and selectivity of the catalytic oxidation of PG and CG through the Au/TiO 2 catalyst system in an aqueous glycerol solution and an atmospheric pressure environment. In PG oxidation, the conversion of glycerol and the selectivity to DHA are 45% and 64%, respectively.…”
Section: Dhamentioning
confidence: 99%
“…Among a variety of bio-derived carboxylic acids, glyceric acid (GLYA) and lactic acid (LA) are two mostly studied carboxylic derivatives for glycerol oxidation. Noble-metal catalysts based on Au [5][6][7][8], Pt [9][10][11][12][13][14], and Pd [15][16][17] and alloys have been widely investigated for oxidation of glycerol due to their high activity. Recent review papers have suggested that, existing studies have been primarily focused on the compositional dependence of those metal catalysts on the formation of GLYA and LA [1][2][3][4]18].…”
Section: Introductionmentioning
confidence: 99%
“…15,22 Ideally, for its eventual use in any integrated bio-refining process, pyrolysis liquid should be processable to the desired value added product from this impure state. 23 Transesterification is an industrially applied technology that can transfer hydroxyls onto to methacrylate monomers. 24 Our approach uses a transesterification of an industrially produced pyrolysis liquid to generate monomers.…”
Section: Introductionmentioning
confidence: 99%